2015
DOI: 10.1039/c5cp00940e
|View full text |Cite
|
Sign up to set email alerts
|

Roles of transition metals interchanging with lithium in electrode materials

Abstract: Roles of antisite transition metals interchanging with Li atoms in electrode materials of Li transition-metal complex oxides were clarified using a newly developed direct labeling method, termed powder diffraction anomalous fine structure (P-DAFS) near the Ni K-edge. We site-selectively investigated the valence states and local structures of Ni in Li0.89Ni1.11O2, where Ni atoms occupy mainly the NiO2 host-layer sites and partially the interlayer Li sites in-between the host layers, during electrochemical Li in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…[9,14] Furthermore,i tw as reported that Ni 2 + ions in the Li + layer led to structural instability and therefore to increased irreversible specific capacity losses. [33] In accordance with the results obtained in this work, Co-free LiMO 2 active materials cannot competew ith LCO in terms of the electrochemical performanceo wing to the disadvantageously high amount of Ni 2 + ions and thus the increased degreeo fL i + /Ni 2 + cation mixing. In this regard, it was also reportedt hat detrimental Li + /Ni 2 + cation mixingc ould be diminished by adding Co 3 + ,w hich thus illustrates its still-indispensable role for stabilizing the structure of LiMO 2 cathodes.A sd isplayed in Figure 8, the implementation of addi-tionalC o 3 + to yield NMC442 and NMC111 results in increased structural stability relative to Co-free NMC550 with regardt ot he reversible extractable amount of Li + ions.T his leads to the conclusion that ad ecrease in undesired Ni 2 + ions is beneficial for the stability and specific energyo ft he resultingL iMO 2 material, even thought his is associated with ad ecrease in beneficial Mn 4 + ions and with an increase in chemically instable Co 3 + .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…[9,14] Furthermore,i tw as reported that Ni 2 + ions in the Li + layer led to structural instability and therefore to increased irreversible specific capacity losses. [33] In accordance with the results obtained in this work, Co-free LiMO 2 active materials cannot competew ith LCO in terms of the electrochemical performanceo wing to the disadvantageously high amount of Ni 2 + ions and thus the increased degreeo fL i + /Ni 2 + cation mixing. In this regard, it was also reportedt hat detrimental Li + /Ni 2 + cation mixingc ould be diminished by adding Co 3 + ,w hich thus illustrates its still-indispensable role for stabilizing the structure of LiMO 2 cathodes.A sd isplayed in Figure 8, the implementation of addi-tionalC o 3 + to yield NMC442 and NMC111 results in increased structural stability relative to Co-free NMC550 with regardt ot he reversible extractable amount of Li + ions.T his leads to the conclusion that ad ecrease in undesired Ni 2 + ions is beneficial for the stability and specific energyo ft he resultingL iMO 2 material, even thought his is associated with ad ecrease in beneficial Mn 4 + ions and with an increase in chemically instable Co 3 + .…”
Section: Resultssupporting
confidence: 88%
“…Mixing of the Li + /Ni 2+ cations decreases the interlayer distance of the Li + layer, which retards the transport kinetics of the Li + ions within the active material during operation and consequently deteriorates the electrochemical performance, especially at increased current rates . Furthermore, it was reported that Ni 2+ ions in the Li + layer led to structural instability and therefore to increased irreversible specific capacity losses . In accordance with the results obtained in this work, Co‐free LiMO 2 active materials cannot compete with LCO in terms of the electrochemical performance owing to the disadvantageously high amount of Ni 2+ ions and thus the increased degree of Li + /Ni 2+ cation mixing.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic distances between Ti and apical (O 2 -1) and basal (O 1 ) oxygen atoms are observed to subtly elongated during the same process. This expansion of distorted TiO 6 octahedron is in accordance with bond length increase often observed during transition-metal reduction in MO 6 octahedra. In general, a less distorted TiO 6 octahedron resulted as Ti atom shifts toward the basal plane of square pyramid (or “octahedron center”).…”
Section: Resultssupporting
confidence: 76%
“…6,35 In the Ni Li Kedge of the XANES spectrum in Li 0.89 N i1.11 O 2 with 11% Li/Ni cation mixing, a shi of the absorption edge does not occur and the Ni valence does not change when the Li amount decreases. 54 The formation energies of Li/Ni, Li/Co, Li/Mn where the amounts of Ni and Mn are the same. 16 In the case of NCM523, such as NCM, the 180 arrangement of the antiferromagnetic Ni 2+ -O-Ni 2+ is stabilized by a strong super exchange interaction.…”
Section: Li/ni Cation Mixingmentioning
confidence: 99%